Avaliação das propriedades físicas e mecânicas do compósito cimento-madeira utilizando farinha de madeira Pinus com cimento portland - Damas, Thyago de Silos (2024)
This work aimed to evaluate the physical and mechanical properties of low-density wood-cement composite, using Pinus spp. wood flour sourced from the waste reuse of timber industries and high early strength Portland cement (CPV-ARI).For the preparation of the tests, a reference mix ratio of 1:3 (cement:sand) by mass was used, and the mass percentages of wood flour were 0%, 5%, 10%, 15% and 20% relative to the cement mass, without additive and with 3% calcium chloride-based set accelerator additive. For each mix, six test specimens were produced and their physical properties (density, water absorption by capillatity and immersion absorption) and mechanical properties (flexural tensile strength, compressive strength, dynamic and static modulus of elasticity, and modulus of rupture) were evaluated. The results showed that density, water absorption, and porosity are interrelated physical properties, and flexural tensile strength, compressive strength, dynamic and static modulus of elasticity, and modulus of rupture are mechanical properties that have a high correlation with density and wood content. Among the evaluated properties, the static modulus of elasticity was the only one that did not obtain the minimum acceptable value of 4,000 MPa in any sample. Furthermore, the addition of the additive generally did not improve the evaluated properties of the composite. Therefore, it is concluded, that the values obtained for the physical and mechanical properties of the wood-cement composite mostly met the values stipulated in the standards and cited research as minimum acceptable criteria.